Breves consideraciones en torno a la reacción pagana: 384- 410 a. D - Pérez Medina, María (Studia Historica. Historia Antigua, 2010)
SUMMARY: The pagan-christian conflict from second middle fourth century a.D. onward presents us the problema about the reasons that impel to these last pagans to defend the traditional ideals. The battle in favour of the survival against the implantation of a new order, explains us the reasons of this anachronical resistance.